Placebo response rates in antidepressant trials: a systematic review of published and unpublished double-blind randomised controlled studies - Furukawa, T; Cipriani, A; Atkinson, L; Leucht, S; Ogawa, Y; Takeshima, N; Hayasaka, Y; Chaimani, A; Salanti, G (Lancet, 2016)
Background: Previous studies have shown that placebo response rates in antidepressant trials have been increasing over the years since 1970s. However, these studies have been based on outdated or limited datasets and used inappropriate statistical methods. Methods: We conducted a systematic review of published and unpublished placebo-controlled double-blind randomised controlled trials of first- and second-generation antidepressants for acute treatment of major depression in adults (update: January 2016). The log-transformed proportions of response, defined as 50% or greater reduction in depression severity from baseline, were meta-analytically synthesized and the structural break point in their secular changes was examined. The influence of the study year and other trial and patient characteristics on the response rates was examined through meta-regression. Findings: We identified 252 placebo-controlled trials (26,324 patients on placebo) between 1978 and 2015. There was a structural break in 1991, and the average placebo response rates in antidepressant trials have remained constant in the range between 35-40% since then (relative risk (RR) 1.00, 95% CI 0.97 to 1.03, for every five-year increase). The reported influence of the study year before 2000 was replicated (RR 1.10, 95% CI 1.05 to 1.15) but became non-significant (RR=1.04, 95% CI 0.99 to 1.09) when controlled for trial methodological factors such as the study duration and the number of study centres. Interpretation: Contrary to the widely-held belief, the average placebo response rates in antidepressant trials have been staying the same for more than 25 years. This new evidence will have an impact on the interpretation of the scientific literature and the future of psychopharmacology, both from a clinical and methodological point of view.